Culturalization and Digitalization as the Focal Areas of Higher Education in the Field of Culturology and Arts as well as Higher LIS Education - V. M. Sheyko; N. M. Kushnarenko (Культура України, 2020)
The relevance of the subject of this study is determined by the necessity of implementation of culturalization and digitalization into higher education in the field of culturology and arts as well as higher LIS education. Research methodology. The authors identify the focal areas of culturalization and digitalization of higher education in the field of culturology and arts as well as higher LIS education in Ukraine drawing on the cognitive possibilities of systemic, culturological and information approaches and problem analytical analysis with special reference to the Kharkiv State Academy of Culture (KhSAC). Results. The authors of this paper give an insight into culturalization and digitalization as the focal areas of improving the quality of higher education in the field of culturology and arts as well as higher LIS education. The study identifies the basic trends of using the processes of culturalization and digitalization in educational and research activities of KhSAC. The paper also deals with the role of culturological competences and network connections in developing the innovative educational and research environment of institutions of higher education which is favorable for generating, transmitting and using new knowledge. The paper analyzes the academic disciplines of culturological and information cycles for some fields of education and specialities implemented at KhSAC. Novelty. The study is an attempt to examine for the first time the culturalization and digitalization as the areas of priority for improving the quality of higher education in the field of culturology and arts as well as higher LIS education in Ukraine. The practical significance. The results of this study can be used by institutions of higher education in the field of culture and arts of Ukraine to create a harmonious culturological and information environment based on the principles of culturalization and digitalization.